A monoclonal antibody‐based indirect competitive enzyme‐linked immunosorbent assay to quantify swertiamarin and related compounds in Swertia japonica Makino. Issue 4 (5th October 2020) - Nuntawong, Poomraphie; Horikawa, Taiki; Ochi, Akihiro; Wada, Shinji; Tsuneura, Yumi; Tanaka, Hiroyuki; Sakamoto, Seiichi; Morimoto, Satoshi
Abstract: Introduction: Swertia japonica Makino ( S. japonica ) has a long history of use as a folk medicine, and it is one of the three essential Japanese folk medicines. S.japonica has been reported to have various biological activities. The biologically active secoiridoid glycoside swertiamarin (SM) has been isolated from S. japonica . The efficacy of this plant is attributed to SM and related secoiridoid glycosides. To control the quality of S. japonica for medicinal use, a method for the determination of SM and other secoiridoid glycosides in the plant is needed. Objective: To produce an anti‐SM monoclonal antibody (MAb) and develop an indirect competitive enzyme‐linked immunosorbent assay (icELISA) for S. japonica standardisation and quality control. Methodology: SM was conjugated to cationised bovine serum albumin (cBSA), and the SM–cBSA conjugate was used to immunise BALB/c mice. Splenocytes from the immunised mice were then fused with SP2/0 myeloma cells to produce hybridoma cells that expressed anti‐SM MAb. Results: The developed icELISA was sufficiently sensitive and had a quantitative range of 0.78 to 12.5 μg/mL. Coefficients of variation below 10% indicated good repeatability. Recoveries in a spike and recovery assay ranged from 91.84% to 115.50%, which confirmed that the icELISA was accurate. The SM content measured using the icELISA was in agreement with the results of a high‐performance liquid chromatography‐ultraviolet (HPLC‐UV) assay. Conclusion: The icELISA is suitable for the high‐throughput analysis of SM and other secoiridoid glycosides in S. japonica . The method is fast, economical, and reliable for S. japonica quality control. Abstract : Here, we produced an anti‐swertiamarin (SM) monoclonal antibody (MAb D2) and applied it to develop an indirect competitive enzyme‐linked immunosorbent assay (icELISA) for quality control of Swertia japonica Makino, which has a long history as Japanese folk medicine. By taking advantage of wide cross‐reaction of MAb D2, present icELISA enabled the determination of total amounts of secoiridoid glycosides of SM, sweroside, and gentiopicroside. Validation analysis supported high precision and accuracy of the icELISA for the quality control of S. japonica.